NEEDS DRIVEN RESEARCH IN AUTOMOBILE ENGINEERING AND TECHNOLOGY FOR SUSTAINABLE INDUSTRIAL AND NATIONAL DEVELOPMENT IN BAYELSA STATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
This study employed descriptive survey research design. The study was conducted in Bayelsa State, Nigeria. Two research questions were formulated to guide the study. The population of the study comprised of 30 respondents. A simple random sampling technique was used. A structured questionnaire was used as instrument for data collection. the instrument was sub-divided into 2 sections, section A and B. Section A, contains 16 items and section B, contains 22 items, making a total of 38 items on a five-point scales, ranging from strongly agreed = 5, agreed = 4, undecided = 3, disagreed =2 and strongly disagreed = 1. The instrument was validated by three experts. Cronbach alpha reliability coefficient index was used to determine the internal consistency of the instrument. The reliability coefficients obtained for the two segments of the questionnaire were 0.78 and 0.86. The overall reliability index for the instrument was 0.82. Data were analyzed using mean and standard deviation, any items with the mean score of 3.50 and above were regarded as agreed and accepted, while any item with the mean score less than 3.50 were regarded as disagreed and not accepted. The results revealed among others issue of brain drain, non-cohesion between educational curriculum and industries, non-aligning research objectives with specific societal needs. It was recommended among others that government should establish national research priorities aligned with development goals.
Keywords: Automobile technology; engineering and technology; needs-driven research